2020
DOI: 10.1002/edn3.165
|View full text |Cite
|
Sign up to set email alerts
|

Linking bacterial diversity to floral identity in the bumble bee pollen basket

Abstract: We are only just beginning to understand the diversity of microbes associated with bee health and reproductive fitness (McFrederick et al., 2017;Steffan et al., 2019). These include viruses, fungi, and bacteria, which compose a wide range of interactions with bees and primarily introduced during foraging and feeding on flowers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…High levels of diversity were expected in pollen provisions, as even though there are usually a few core phyla present, there is generally great diversity at a species level in plant microhabitats (Ambika Manirajan et al, 2016). Studies of bumble bee pollen baskets have also shown that plant and bacterial alpha diversity are correlated (Sookhan et al, 2021). This correlation in diversities does not extend to bee microbial diversity, however; rather, it may be mainly the core bacteria from provisions that are acquired and maintained within bee hosts (McFrederick & Rehan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of diversity were expected in pollen provisions, as even though there are usually a few core phyla present, there is generally great diversity at a species level in plant microhabitats (Ambika Manirajan et al, 2016). Studies of bumble bee pollen baskets have also shown that plant and bacterial alpha diversity are correlated (Sookhan et al, 2021). This correlation in diversities does not extend to bee microbial diversity, however; rather, it may be mainly the core bacteria from provisions that are acquired and maintained within bee hosts (McFrederick & Rehan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Snodgrassella adhering to the gut wall suggests stronger host-specific interactions, and therefore it is more likely to be transmitted vertically or through oral trophallaxis ( Kwong et al, 2017 ; Cornet et al, 2022 ). On the other hand, Gilliamella may be transmitted outside the nest environment ( e.g ., through flowers), although the prevalence of this mode of transmission needs to be verified with more studies ( Koch et al, 2013 ; Graystock, Goulson & Hughes, 2015 ; Sookhan et al, 2021 ). The differences in the strength of interactions with host tissues, and the ability to survive outside of the gut environment thus likely explain differences in host specificity, and, potentially, cospeciation patterns between G. apicola and S. alvi .…”
Section: Discussionmentioning
confidence: 99%
“…This allows them to foster very stable core microbiomes composed of eight bacterial phylotypes that contribute up to 95% of the overall gut microbial load (Engel et al, 2012;Kwong & Moran, 2016;Martinson et al, 2011). In comparison, solitary and facultatively social bees gain more of their microbiomes from their environment (Cohen et al, 2022;Dew et al, 2020;Graystock et al, 2017;Keller et al, 2021;McFrederick et al, 2012McFrederick et al, , 2017, bolstering more variable microbiota (Dew et al, 2020;McFrederick et al, 2017;Sookhan et al, 2021). Studies focusing on wild bee microbiomes are currently limited yet remain ongoing (Chau et al, 2023;Cohen et al, 2020;Handy et al, 2022;Kapheim et al, 2021;Nguyen & Rehan, 2023a;Shell & Rehan, 2022).…”
Section: Introductionmentioning
confidence: 99%